2002
DOI: 10.1128/aem.68.11.5231-5240.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Adaptive Response to Trichloroethylene-Mediated Stresses in Ralstonia pickettii PKO1

Abstract: In Ralstonia pickettii PKO1, a denitrifying toluene oxidizer that carries a toluene-3-monooxygenase (T3MO) pathway, the biodegradation of toluene and trichloroethylene (TCE) by the organism is induced by TCE at high concentrations. In this study, the effect of TCE preexposure was studied in the context of bacterial protective response to TCE-mediated toxicity in this organism. The results of TCE degradation experiments showed that cells induced by TCE at 110 mg/liter were more tolerant to TCE-mediated stress t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The hydroxyl group of Thr-107 may form a hydrogen bond with the backbone carbonyl of Gly-103 supporting the orientation of this residue in a way that directs the C-4 in toluene toward the diiron center (forming only p-cresol) or the C-2 in naphthalene, resulting in 2-naphthol formation. DISCUSSION Toluene monooxygenases have been the subject of many studies in the past few years because of their bioremediation capabilities as well as their potential as biocatalysts for green chemistry (8,16,39,40). Much effort has been placed on understanding the mechanisms by which these complex enzymes work and on the role of various active site residues in activity and selectivity.…”
Section: Table II Regiospecific Oxidation Of Toluene (With Rate) Nbmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydroxyl group of Thr-107 may form a hydrogen bond with the backbone carbonyl of Gly-103 supporting the orientation of this residue in a way that directs the C-4 in toluene toward the diiron center (forming only p-cresol) or the C-2 in naphthalene, resulting in 2-naphthol formation. DISCUSSION Toluene monooxygenases have been the subject of many studies in the past few years because of their bioremediation capabilities as well as their potential as biocatalysts for green chemistry (8,16,39,40). Much effort has been placed on understanding the mechanisms by which these complex enzymes work and on the role of various active site residues in activity and selectivity.…”
Section: Table II Regiospecific Oxidation Of Toluene (With Rate) Nbmentioning
confidence: 99%
“…TbuC is an NADH oxidoreductase (36.1 kDa) that is responsible for the transfer of electrons from reduced nucleotides via the redox center to the terminal oxygenase (13). R. pickettii PKO1 cells expressing the TpMO pathway were shown to degrade trichloroethylene when induced by toluene or trichloroethylene (16,17).The original characterization of TpMO as a meta-hydroxylating enzyme that is capable of transforming toluene to mcresol (18) was found to be incorrect, as Wood and co-workers (19) have shown that TpMO produces 90% p-cresol and 10% m-cresol from toluene and successively oxidizes these to 4-methyl catechol. This result is in agreement with the work of Tao et al (20) and Vardar and Wood (21), which shows that the four monooxygenases, TpMO, toluene 4-monooxygenase (T4MO) of Pseudomonas mendocina KR1, toluene ortho-monooxygenase (TOM) of Burkholeria cepacia G4, and toluene o-xylene monooxygenase (ToMO) of Pseudomonas stutzeri OX1 hydroxylate benzene successively to phenol, catechol, and 1,2,3-trihydroxybenzene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidizing enzymes are of great potential to the chemical and pharmaceutical industries due to their high regio-, chemo-, and stereoselectivity and their ability to facilitate reactions with chemically stable substrates (1, 2). Due to their complexity, biological oxidation reactions are often performed using growing or resting cells (17).One important group of bacterial oxygenases includes the toluene monooxygenases, which have additional potential applications in bioremediation (23,30,32). The aerobic biodegradation of toluene is well studied, and the pathway is available at the University of Minnesota databank (9).…”
mentioning
confidence: 99%
“…One important group of bacterial oxygenases includes the toluene monooxygenases, which have additional potential applications in bioremediation (23,30,32). The aerobic biodegradation of toluene is well studied, and the pathway is available at the University of Minnesota databank (9).…”
mentioning
confidence: 99%